Morphology of Lip Prints in Ethnic Meitei Subjects : A Preliminary Analysis of Patterns and Sexual Variation - Haricharan , A; Memchoubi , P H; Devi , S E; Salam , S; Devi , T M (Journal of Indian Academy of Forensic Medicine, 2023)
Lip prints are individualistic and can be helpful in verifying a person’s presence at the crime scene. This cross sectional study aims to classify lip prints in ethnic Meitei population and determine whether sex differences exist. Estimated sample size is 250. Lip prints of 137 females and 113 males were obtained using dark-colored lipstick and cellophane tape. Lip prints were analyzed using a magnifying lens and classified according to the Suzuki and Tsuchihashi classification. The upper and lower lips of males and upper lips of females revealed Type II to be the predominant pattern, accounting for 19%, 13.8% and 22% of all occurrences, respectively. In females, a Type I pattern was the most frequent in the lower lips (22%). These differences were statically significant (p < 0.001). A correlation analysis, with Spearman’s rank order correlation (rho), was used. The strength of the linear relationship between the lip patterns for the upper and lower lips (right and left sides) and sex was analyzed. We found a medium correlation value (from 0.030 to 0.412) with statistical significance (p < 0.005) for upper right lip and lower left lip with the exception of the upper left lip (correlation value = 0.092 , p = 0.147 & ) and lower right lip (correlation value = 0.030, p = 0.642). This study corroborates the hypothesis that lip prints may be useful in sex determination.